Estudo geoecológico da paisagem costeira do município de Raposa – MA: bases para o planejamento ambiental - LYRA, Ingrid Nicolly Oliveira (2022)
In Raposa - MA, urban expansion has brought a series of environmental problems that are increasingly degrading the landscape due to the lack of planning for the use of physical space. These and other reasons motivated the development of this research, therefore the main objective was to realize a study of the coastal landscape of the municipality of Raposa - Maranhão in order to provide a basis for the creation of an environmental zoning proposal suited to the reality of the area. The geoenvironmental, historical and socioeconomic components of the area were described, in addition to the current characterization of the coastal landscape of the municipality from the subdivision of geoecological units, finally it was possible to diagnose the current situation of the landscape and propose the functional zoning. The methodology of this study is based on the Geoecology of Landscaps. Thus, the following steps were adopted: a) organization and inventory phase; b) analysis phase; c) diagnostic phase and d) propositional phase. The landscape mapping allowed the classification into 20 geoecological subunits, through which they were analyzed and discussed based on the different types of use/occupation and main problems. The landscape diagnosis considered the evaluation of the subunits based on environmental aspects of a natural and anthropic nature, such as wind power, deforestation, among others. From the results of landscape diagnosis, it was concluded that 71.12% of the total área were defined as stable, without degradation and in a favorable situation, explained by the extensive area of preserved mangroves (32.41 km²) that can still be found in the municipality. The remaining 28.88% present an environmental situation that varies from moderately favorable to unfavorable. At the end of the study, the following zones were established: Environmental Preservation, Environmental Conservation, Environmental Improvement, Disciplined Use and Cultural Preservation, in which it was possible to highlight guidelines to conserve and preserve natural resources and assist in the sustainable development of human activities.